Women as Canang Sari Street Vendors in Bali - Atmadja, Anantawikarama Tungga; Ariyani, Luh Putu Sri; Atmadja, Nengah Bawa (KOMUNITAS: INTERNATIONAL JOURNAL OF INDONESIAN SOCIETY AND CULTURE, 2016)
Every Hindu family in Bali dedicates offerings of Canang Sari on a daily basis. The provision of the offering is not always created by them, but they buy canang sari. This has turned canang sari into a market commodity. Therefore, women have emerged as canang sari street vendors in the several towns in Bali. This study examines the reasons why women do this job, especially in Singaraja Regency. The approach of this research was qualitative study which focused on critical social theory. The results show that the reasons women do such business activities not solely because canang sari street vendors is an informal economic sector, but also it is related to the ownership of economic, social, cultural, and symbolic capitals. This reason is strengthened by the condition of Balinese who have affected by McDonaldization society so they prefer to buy canang sari rather than making it their own.